Application of Augmented Reality Technology with the Fuzzy Logic Method as an Online Physical Education Lecture Method in the New Normal Era - Albar, C. N.; Widiansyah, M. Givaldi; Mubarok, S.; Aziz, M. A.; Maulana, Hanhan (Indonesian Journal of Multidiciplinary Research, 2021)
This research aims to create Augmented Reality about basic physics practicum tutorials on the Sound Wave Resonance module in the Department of Computer Systems at the Universitas Komputer Indonesia (UNIKOM) based on Android. The advantages of this technology can be used as a medium of online learning if there is an emergency that results in not implementing conventional learning so that learning activities remain effective. This application program is intended to facilitate the Lecturer / Laboratory Assistant in presenting the material as well as attracting student learning interest in practicum learning. The method used in this study was a qualitative method by describing the condition of the Basic Physics Laboratory in the computer engineering department, and the system development method used is the paradigm method, Waterfall. Data was collected through interviews with the Chair of the Basic Physics Laboratory. This study results obtained an information system that allows the practitioner to compare the calculations' results mathematically with the application, and practicum can understand the material easily and fun.